A PROTECTION COPYRIGHT REGISTRATION CULTURE - Isnaini, Atin Meriati; Lisyanigrum, Novita; Sari Lukman, Dwi Ratna Kamala; Alfarizi, Lalu Mariawan (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2023)
Folklore is part of traditional knowledge, cultural traditions within the scope of art, literature and science. Folklore is one of the intellectual property rights of the community that must be given legal protection in an effort to preserve the nation's culture. Legal protection of folklore is carried out based on three considerations; (1) the development of national character in traditional knowledge, (2) the enactment of intellectual property rights regimes and folklore (3) economic value. Folklore protection shows the existence of a culture, emphasizing the identity or characteristics of a region. The Foklor dispute that occurred in International is one example, where the original culture (folklor) from Indonesia is claimed by Malaysia as the original culture of its country such as Reog Ponorogo, Pendet Dance, Gondang Sembilan. So it needs concern from the government both central and regional to preserve the nation's culture and legal protection as an intellectual work culture. Legal protection that can be done by registering Copyright to the Directorate General of IPR of the Republic of Indonesia and International through WIPO (World Intellectual Property Organization).